Turkey, a Century of Change in State and Society
XI, 210 p. 5 illus., 2 illus. in color.
Keywords: The Republic of Turkey celebrates the centenary of its proclamation in 2023. Founded on the ruins of the Ottoman Empire, one of the world’s greatest empires both in terms of its geographical extent and its longevity, Republican Turkey has gone through a century of profound and constant changes and transformations from politics to society, economy to religion, or culture to history. These changes have been produced by inner and foreign policies carried out and implemented by the country’s leaders – from Atatürk, the founder of modern Turkey to Recep Tayyip Erdoğan, the current Turkish President in 2023 - but also under the influence of the regional and international context. This collective work aims to take stock of the great achievements of the Turkish republican project. It attempts to draw a general presentation of the evolution of contemporary Turkey in six main areas which constitute six major issues for the country: the general political evolution of Turkey focusing on the issueof citizenship; the transformations in the Turkish economy through a political economy analysis; the evolution of the relationship between religion, state and society; Turkey’s nation-building and the Kurdish question, which still seeks a solution; the changes in Turkish foreign policy focusing on the relationship between Turkey and the West; the relationship between Turkey and Europe, caught between the model of civilization for the republican regime and the prospects of accession to the European Union. Several “focus points” also concentrate on specific subjects such as the Alevi issue, the Cyprus issue or the Turkish soft power with an accent on Africa. Bayram Balci is CNRS researcher at CERI-Sciences Po Paris. His works and publications are related to religion and politics in Turkey, Central Asia, the Caucasus, and the Middle East. Nicolas Monceau is Associate Professor of Political Science, University of Bordeaux, France. His research focuses on Turkish Politics and Turkey in its regional and international environment. He has published several books on Turkey and the Middle East, Turkey and the EU and the Turkish elite.